1999
DOI: 10.1063/1.123029
|View full text |Cite
|
Sign up to set email alerts
|

Diamond/Ir/SrTiO 3 : A material combination for improved heteroepitaxial diamond films

Abstract: Heteroepitaxial diamond films with highly improved alignment have been realized by using the layer sequence diamond/Ir/SrTiO3(001). In a first step, epitaxial iridium films with a misorientation <0.2° have been deposited on polished SrTiO3(001) surfaces by electron-beam evaporation. Using the bias-enhanced nucleation procedure in microwave plasma chemical vapor deposition, epitaxial diamond grains with a density of 109 cm−2 could be nucleated on these substrates. The orientation relationship for this la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…The BEN step was performed for 45 min at a temperature of about 800°C, a gas pressure of 30 mbar and a microwave power of 1100 W using a process gas mixture with 7% CH 4 in H 2 . The bias voltage of about 280 V was applied to a circular anode while the sample holder was at ground potential [7]. A diamond reference sample with a thickness of 13 µm was grown for 30 h at a reduced methane concentration of 1%, at identical temperature, pressure and microwave power without applied bias voltage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BEN step was performed for 45 min at a temperature of about 800°C, a gas pressure of 30 mbar and a microwave power of 1100 W using a process gas mixture with 7% CH 4 in H 2 . The bias voltage of about 280 V was applied to a circular anode while the sample holder was at ground potential [7]. A diamond reference sample with a thickness of 13 µm was grown for 30 h at a reduced methane concentration of 1%, at identical temperature, pressure and microwave power without applied bias voltage.…”
Section: Methodsmentioning
confidence: 99%
“…On iridium the diamond grains exhibit an unmatched degree of initial alignment together with an extraordinarily high density [7] which resulted in the first successful deposition of single crystal diamond films via heteroepitaxy [8]. In recent publications it was shown that single crystal iridium films can be integrated on silicon substrates via oxide buffer layers [9].…”
Section: Introductionmentioning
confidence: 99%
“…As described in the introduction, a certain film thickness of the diamond with an appropriate textured growth technique is necessary to obtain a highquality surface of heteroepitaxial diamond because dense defects exist around the boundary between the film and substrate (Ir). 3,6,8) Typical values of the FWHM observed for heteroepitaxially grown diamond on Ir as continuous films by a normal method in our laboratory are about 10-20 cm…”
Section: Resultsmentioning
confidence: 99%
“…19) However, a certain film thickness of the diamond with an appropriate textured growth technique is necessary to obtain a high-quality surface of heteroepitaxial diamond because dense defects exist around the boundary between the film and substrate (Ir). 3,6,8) Epitaxial lateral overgrowth (ELO) is a commonly employed technique to minimize the defect densities in several materials epitaxially grown on lattice-mismatched substrates. [20][21][22][23] Since the lattice mismatch between Ir and diamond is approximately 7%, reduction of the defect density in heteroepitaxial diamond can be expected by ELO.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the substrates that have shown limited success with obtaining few layers of diamond on limited areas are silicon, silicon carbide, nickel, cubic boron nitride and iridium [12]. Iridium is the best-known substrate giving the lowest angle spread of diamond-crystal orientation [13]. The limitation, however, is that free-standing single-crystal iridium wafers are not yet available.…”
mentioning
confidence: 99%